Although this problem is best suited for a calculator, here are some insights:
Whenever you are subtracting a negative number, the effect is the same as ADDING a POSITIVE number:
-3.4 - (-7.6) = -3.4 + 7.6
Also, since addition is "commutative", it's OK to switch the order of the terms on the right side:
= 7.6 + (-3.4)
Finally, since adding a negative number is the same as SUBTRACTING a POSITIVE number, we could re-write this expression:
= 7.6 - 3.4 (I find this easier to do)
= 4.2
I hope this sheds some light on the order of operations and the Commutative Property.
2006-11-08 09:58:47
·
answer #1
·
answered by Tim GNO 3
·
1⤊
0⤋
-3,4
+7.6[add the opposite]
do the rest yourself.
this is eayeasy homework
2006-11-08 17:59:31
·
answer #2
·
answered by SOMEONE! 3
·
0⤊
0⤋
(-3.4) -( -7.6) = X
(3.4) + (-3.4) - (-7.6) = X + 3.4
(-7.6) + (-1)(7.6) = X + 3.4 - 7.6
(-1) = X + 4.2
-X = 4.2
(-1)(-X) = (-1)(4.2)
X = (-4.2)
2006-11-08 18:04:02
·
answer #3
·
answered by Scarp 3
·
0⤊
0⤋
4.2
-3.4 - (-7.6) = -3.4 + 7.6 = 7.6 - 3.4 = 4.2
2006-11-08 17:55:23
·
answer #4
·
answered by teaspoons 1
·
0⤊
0⤋
-3.4-(-7.6)=-3.4+7.6=7.6-3.4=4.2
The answer is 4.2
2006-11-08 17:55:25
·
answer #5
·
answered by Lnc 1
·
0⤊
0⤋
-3.4 - (-7.6)
= -3.4 + 7.6 "-(-) = +"
= 7.6 - 3.4
= 4.2
2006-11-08 17:54:52
·
answer #6
·
answered by bourqueno77 4
·
0⤊
0⤋
don't you have a calculator?
-12-(-42)
-12+42
=30
2006-11-08 17:54:04
·
answer #7
·
answered by pffff 2
·
0⤊
0⤋
(-3.4) - (-7.6) = 4.2
2006-11-08 17:57:50
·
answer #8
·
answered by DanE 7
·
0⤊
0⤋
4.2
2006-11-08 17:54:10
·
answer #9
·
answered by memotonemo2 2
·
0⤊
0⤋